Candangos: occupational reconstruction as a tool to understand social problems and transformative action in the utopian city of Brasília/ Candangos: teoria da reconstrução ocupacional como uma ferramenta para a compreensão de problemas sociais e ações transformativas na utópica cidade de Brasília - Dos Santos, Vagner; Frank, Gelya; Mizue, Ana (Cadernos Brasileiros de Terapia Ocupacional, 2020)
Teaching an occupational therapy agenda of social transformation in Brazilian universities is an ongoing project. In this article we (1) Introduce the theory of occupational reconstructions; (2) Contextualize the candangos’ – those who built the country’s new utopian Brazilian capital, Brasília - situation based on published literature; (3) Describe reforms to expand social inclusion at University of Brasília, Brazil; and (4) Discuss how occupational reconstruction served as a frame for teaching, research and practice. Occupational reconstruction theory explains social transformation as part of the philosophy and knowledge base of ‘occupation’. The theory was useful to guide the students’ experiences and reach learning outcomes. During the course, students began by recounting their histories while also contacting their elders to find out how the candangos dealt with problematic social conditions in Brasília’s early days. They were challenged to present a case of the occupational reconstruction as an example of literatura de cordel– a low-budget printed booklet; thus, moving the candangos’ stories into the public sphere. The paper concludes with a critical reflection on the advantages, limitations, and possible future applications of the curriculum.